Pengaruh Perubahan Peta Hazard Gempa Indonesia terhadap Perencanaan Perkuatan Lereng Menggunakan Soil Nailing - Rani Anggraini; Dio Alif Hutama; Isnaniati . (Universitas Muhammadiyah Surabaya, 2018)
AbstractRevision of Indonesia seismic hazard maps is the improvement of the 2010 hazard maps. In this revision, it was found that the design seismic load has been changed for several regions, one of them was Bojonegoro regency. So it is necessary to evaluate the value of the safety factor (FS) of the slope. The aim of this study was to compare FS of slopes reinforced with soil nailing due to the 2010 and 2017 seismic loads on internal and external stability by using two calculation methods, namely manual calculation and Rocsience Slide 6.0 program. The variation used in this study was vertical spacing of reinforcement (Sv = 1), the ratio of the length of the reinforcement and the height of the slope (L/H), the reinforcement angle(θ). The results of the analysis show the decreasing of safety factor(FS)for unreinforced slope due to changes in the 2010 to 2017 seismicload of 4,0% calculated using Slide 6.0. Internal stability of pullout decreased about 13,04% - 17,08%.Internal stability of rupturedecreased about 0,77% - 34,3%. External stability against sliding shows the decreasing of FS about9,1% - 12,9%.External stability against bearing capacity failure shows the decreasing of SF about10,8% - 11,0%. Global stability shows the decreasing of SF about 4,6% - 8,9%.Keywords:Indonesia Seismic Hazard Maps,Slope, Soil Nailing, Slide 6.0AbstrakRevisi peta gempa hazard Indonesia 2017 merupakan penyempurnan dari peta gempa hazard 2010. Pada revisi tersebut ditemukan perubahan beban gempa pada beberapa daerah dimana salah satunya adalah kabupaten Bojonegoro, sehingga perlu dilakukan evaluasi terhadap nilai faktor keamanan (FS) pada lereng. Penelitian ini bertujuan untuk membandingkan FS lereng dengan perkuatan soil nailing akibat beban gempa 2010 dan 2017 pada stabilitas internal dan stabilitas eksternal dengan mengnggunakan dua metode perhitungan yaitu perhitungan manual dan program Rocsience Slide 6.0. Variasi yang digunakan dalam penelitian ini adalah jarak antar perkuatan (Sv = 1), rasio panjang perkuatan dan tinggi lereng (L/H), sudut perkuatan(Ɵ). Hasil penelitian perhitungan Slide 6.0 lereng tanpa perkuatan menunjukkan adanya penurunan besarnya SF dari perubahan beban gempa 2010 ke 2017 sebesar 4,0%. Besarnya penurunan FS putus tulangan berkisar 13,04% - 17,08%. Besarnya penurunan FS cabut tulanga berkisar 0,77% - 34,3%. Besarnya penurunan FS terhadap geser berkisar 9,1% - 12,9%. Besarnya penurunan FS kegagalan daya dukung berkisar 10,8% - 11,0%. Besarnya penurunan FS keruntuhan global berkisar 4,6% - 8,9%.Kata Kunci : Peta Hazard Gempa, Lereng, Soil Nailing, slide 6.0